Adsorption and desorption characteristics of coal seam gas under infrared radiation - Yuying Tu; Yongli Zhang; Yubin Dong; Yulin Ma (Capillarity, 2023)
Infrared radiation technology can enhance rock permeability and promote methane desorption in coalbed methane thermal recovery. In this study, an experimental system with infrared radiation is developed to investigate the adsorption/desorption behavior of coal under different water contents. The results demonstrate that higher power levels of infrared radiation lead to decreased adsorption capacity and increased desorption capacity in coal. Specifically, employing 50 W infrared radiation results in a 30.9% increase in desorption capacity. Higher moisture content intensifies the desorption hysteresis effect, while this adverse impact can be mitigated by infrared radiation with greater power levels, exhibiting a stronger ability to reduce desorption-induced hysteresis. Additionally, a critical pressure for infrared radiation is established. Before and after this pressure, the influence of infrared radiation power on pressure sensitivity differs significantly. Finally, an improved Langmuir adsorption model considering infrared radiation power and moisture content is proposed and validated using experimental data. Our research expands the application of infrared radiation technology for enhanced coalbed methane recovery during actual mining operations. Document Type: Original article Cited as: Tu, Y., Zhang, Y., Dong, Y., Ma, Y. Adsorption and desorption characteristics of coal seam gas under infrared radiation. Capillarity, 2023, 8(3): 53-64. https://doi.org/10.46690/capi.2023.09.02